Appropriate Technology Application in Corn Planting in Kenagarian Limabanang Kecamatan Suliki Kabupaten 50 Kota Sumatera Barat - Ambiyar Ambiyar; Budi Syahri; Junil Adri (Universitas Negeri Padang, 2019)
The problem in this article is that farmers use wood in growing corn seeds to agricultural land. This method requires a long time for farmers to also need a lot of energy in the process of planting corn. To plant 1/2 Ha of cornfield in the planting process it takes 16 working hours with two workers. Problems in the planting process require solutions. One solution that can be used is to make a device that has appropriate technology that is able to streamline work time and energy requirements in planting corn seeds. The application of science and technology carried out is by giving demonstrations and applications directly in the field. The method of applying science and technology conducted in this activity is to provide introductory theories, demonstrations, and practices. In the application of this science and technology, a corn seed planter is made so that farmers can easily plant corn seeds. This is an application of appropriate technology for the community. The steps taken in the manufacture of this machine are: Design of corn planting tools, Manufacture of frames, the process of making corn planter wheels, Manufacture of power delivery shaft, Finishing Process, Integrated process and road testing. When testing, the results obtained are that the machine is able to make the distance between holes towards the front 20 cm long. The distance of the left or right side of the hole is 50 cm. In each hole the machine will plant 2 corn seeds. The time needed by farmers is very short in the planting process which is 40 minutes for half a hectare of corn crop